Ascarids exposed: a method for in vitro drug exposure and gene expression analysis of anthelmintic naïve Parascaris spp. Issue 6 (12th May 2020) - Scare, J. A.; Dini, P.; Norris, J. K.; Steuer, A. E.; Scoggin, K.; Gravatte, H. S.; Howe, D. K.; Slusarewicz, P.; Nielsen, M. K.
Abstract: Ascarid parasites infect a variety of hosts and regular anthelmintic treatment is recommended for all species. Parascaris spp. is the only ascarid species with widespread anthelmintic resistance, which allows for the study of resistance mechanisms. The purpose of this study was to establish an in vitro drug exposure protocol for adult anthelmintic-naïve Parascaris spp. and report a preliminary transcriptomic analysis in response to drug exposure. Live worms were harvested from foal necropsies and maintained in RPMI-1640 at 37 °C. Serial dilutions of oxibendazole (OBZ) and ivermectin (IVM) were prepared for in vitro drug exposure, and worm viability was monitored over time. In a second drug trial, worms were used for transcriptomic analysis. The final drug concentrations employed were OBZ at 40.1 μ m (10 μ g mL −1 ) and IVM at 1.1 μ m (1 μ g mL −1 ) for 24 and 3 h, respectively. The RNA-seq analysis revealed numerous differentially expressed genes, with some being potentially related to drug detoxification and regulatory mechanisms. This report provides a method for in vitro drug exposure and the phenotypic responses for Parascaris spp., which could be extrapolated to other ascarid parasites. Finally, it also provides preliminary transcriptomic data following drug exposure as a reference point for future studies of Parascaris spp.